Quelques indicateurs preliminaires de l'impact des politiques sur le developpement et la commercialisation de la production laitiere en Afrique subsaharienne - Mbogoh, S.G. (1984)
Examines the marketing of domestically produced dairy products in sub-Saharan Africa, including imported but locally reconstituted whole milk powder and butter oil, and discusses trends in the imports of other dairy products over the last two decades in order to assess the impact of various dairy development and marketing policies of governments on the production & consumption of dairy products in the region.